P42 Development of an algorithm for determining the stage of innovation of an invasive procedure or device. (8th April 2021) - Scroggie, D L; Elliott, D; Avery, K; Cousins, S; Blencowe, N S
Abstract: Introduction: The IDEAL framework describes a series of stages through which surgical innovations typically pass. For each stage, the framework makes recommendations with the intention of improving the quality of research in surgery. Its adoption has been slow despite publication of practical guidance. It has been recognized that determining the stage of innovation of an invasive procedure or device can be problematic, and this issue may be hindering adoption of the framework. The aim of this study is to develop a practical algorithm for determining the stage of innovation of any invasive procedure or device. Methods: Multiple data sources will be used: published literature, intra-operative video recording, interviews with stakeholders, healthcare datasets, and clinical policies and guidelines. Systematic reviews will be conducted to identify guidance relating to surgical innovation, and evaluations or critiques of guidance. Case studies of surgical innovations will be undertaken, to gain an understanding of problems encountered in determining stage of innovation. An algorithm will be developed through an iterative process of testing and refinement, triangulating data from the literature reviews and case studies. Results: The findings of the initial systematic reviews will be presented. This will include guidance relating to surgical innovation, and evaluations or critiques of it. Recognized problems in determining stage of innovation will be summarized, including proposed solutions and suggestions for further development. Conclusion: This study will use multiple data sources to develop a practical algorithm for determining the stage of innovation of any invasive procedure or device.